Cytogenetic analysis of coke oven workers in Eastern Slovakia - Sedlák, Vincent; Bujňák, Anton; Gajdoš, Andrej; Gajdošová, Dagmar; Poráčová, Jana; Konečná, Mária; Fejér, Jozef; Gruľová, Daniela; Vašková, Hedviga; Mydlárová Blaščáková, Marta (Central European journal of public health, 2023)
OBJECTIVE: Our study aimed to evaluate the extent of polycyclic aromatic hydrocarbon (PAH) exposure in coke oven workers from Eastern Slovakia by cytogenetic analysis of human peripheral lymphocytes. METHODS: A total of 81 peripheral blood samples were collected from PAH-exposed workers (mean age 45.84 ± 9.73 years) and 30 samples constituted the control group (41.93 ± 15.39 years). The samples were processed using routine cytological analysis. Conventional cytogenetic analysis of human peripheral lymphocytes has been used to evaluate the effects of PAHs. RESULTS: Comparison of the aberrant cells in the total exposed with the controls showed a significant difference (p < 0.05). A high level of significance (p < 0.001) was observed when comparing the gaps between the exposed group and the control group. There was a significant difference (p < 0.01) in aberrant cells and chromatid breaks (p < 0.05) in the GR1 working subgroup compared with the control group. The results of the correlation analysis did not show a significant relationship between the length of occupational exposure and the frequency of aberrant cells (r = 0.071, p = 0.529). Similarly, no association was observed between smoking among coke plant workers and the frequency of aberrant cells (r = 0.117, p = 0.538). CONCLUSION: Cytogenetic analysis showed an increased frequency of chromosomal aberrations in coke oven workers in Eastern Slovakia.
Keywords: Slovakia; Slovenská republika; Occupational Exposure; Pyrenes; Coke; koks; pracovní expozice; Adult; pyreny; dospělí; lymfocyty; polycyklické aromatické uhlovodíky; Polycyclic Aromatic Hydrocarbons; lidé; Humans; Lymphocytes; cytogenetické vyšetření; lidé středního věku; Cytogenetic Analysis; Middle Aged